Social innovation, sustainability and the governance of protected areas: revealing theory as it plays out in practice in Costa Rica. Issue 13 (10th November 2019) - Castro-Arce, Karina; Parra, Constanza; Vanclay, Frank
Abstract : Protected areas (PAs) are social-ecological systems (SES) and are contested spaces. The challenges in governing PAs call for a governance system that works with human-nature relations and is capable of adapting to each PA. This necessitates innovative processes and adaptive governance. This paper contributes to the discussion on adaptive governance in SES by offering empirical evidence from Costa Rica on how the processes of social innovation occur in practice. We discuss the evolving governance of the Juan Castro Blanco National Water Park, particularly the contribution of a local association that drives conservation and management of the park. We show that social mobilisation caused social innovation, which was revealed by the achievement of three interconnected process outcomes: satisfaction of interests; effective socio-political arrangements; and empowerment. The socially-innovative governance of the park has contributed to sustainability and to social-ecological change at many levels.